Effect of particle shape on biomass pyrolysis in a bubbling fluidized bed. (1st May 2023) - Soria-Verdugo, Antonio; Cano-Pleite, Eduardo; Passalacqua, Alberto; Fox, Rodney O.
Highlights: Pyrolysis of beech wood particles in a bubbling fluidized bed was investigated. Effect of beech wood particle shape on their pyrolysis conversion was studied. A high-precision scale was used to measure the beech wood mass evolution. Pyrolysis time is proportional to the particles heat transfer characteristic length. A simple shrinking model proposed can properly predict the effect of particle shape. Abstract: The effect of biomass particle shape on the conversion of beech wood during pyrolysis in a bubbling fluidized bed (BFB) was experimentally quantified. A lab-scale BFB installed on a high-precision scale was used to characterize the mass loss of the biomass particles immersed in the bed. The scale could monitor the mass loss of the beech wood particles while moving freely inside the bed, which was operated at 2.5 times the minimum fluidization velocity of the bed material employed. The tests were performed at 500 and 600 °C using beech wood particles of the same mass, but different in shape. All particles used were cylindrical in shape, with the same mass, and differing in their aspect ratio, analyzing particles from typical biomass chips to standard biomass pellets. The experimental results indicate that the velocity of pyrolysis for the different particles is proportional to the characteristic heat transfer length of the particles, with pyrolysis times ranging from 27 to 53 s for a bed temperature of 600 °C and from 43 to 85 s for a bed temperature of 500 °C. The minimum pyrolysis time was obtained for particles with a diameter of 20 mm and a length of 2 mm pyrolyzing in a bed at 600 °C, whereas the maximum pyrolysis time corresponds to particles of 10 mm in diameter and 8 mm in length converting in a bed at 500 °C. Estimations of the conversion time obtained from a Shrinking Unreacted Particle Model (SUPM), assuming a constant density and reducing volume of biomass during conversion, and a Uniform Conversion Model (UCM), considering uniform volume and decreasing density of biomass along the conversion process, were compared to experimental measurements of the conversion time. Qualitative agreement was found between the experimental values and the predictions of the conversion time from the simplified models, obtaining in all cases conversion times proportional to the characteristic length of heat transfer of each particle shape.